The effects of an intradialytic resistance training on lower extremity muscle functions - Zelko, Aurel; Rosenberger, Jaroslav; Skoumalova, Ivana; Kolarcik, Peter; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (Disability and rehabilitation, 2022)
PURPOSE: The loss of muscle functions is a significant health issue among dialysis patients. Poor muscle strength negatively affects a patient's mobility, independence and quality of life. The aim of the study was to assess the effects of an intradialytic resistance training (IRT) on lower extremity muscle functions among dialysed patients. MATERIALS AND METHODS: Ninety patients were allocated into an experimental group (n = 57) or control group (CNG) (n = 33) according to the location of the dialysis service center. Fifty-eight patients completed the study follow-up. The intervention regarded 12-week IRT, while the controls remained physically inactive during hemodialysis. In both groups of patients, we assessed lower extremity muscle functions by a diagnostics of maximal isometric force generated during hip flexion (HF), hip extension (HE), and knee extension (KE) contractions at baseline, after the 12-weeks intervention and after a further 12-weeks follow up. RESULTS: We found that improvements in HE between baseline and post-intervention were significantly larger for the experimental than the CNG (difference 32.0, 95% CI = 12.3-51.8, p = 0.002). For the other primary outcomes, we found no differences between the groups, and neither for the two other indices of muscle strength (HF and KE). At 12-weeks follow-up, we found no statistically significant differences between the two groups. CONCLUSIONS: Our findings indicate that exercise during dialysis not just suppresses adverse effects in muscle strength and functioning, but effectively and safely increases lower extremities muscle function in a relatively short time.Implications for RehabilitationRegular, progressive, resistance training realized during dialysis is well tolerated and safe for exercise interventions in hemodialysis patients.A 12-weeks intradialytic resistance training is effective in the prevention and clinical management of muscle function loss among hemodialysis patients.The range of improvements in muscle functions, demonstrated by the assessment of maximal isometric force, varied severely during different lower extremity movements of hemodialysis patients.
Keywords: svaly; Resistance Training; Lower Extremity; dialýza ledvin; Muscles; Muscle Strength; Renal Dialysis; hemodialysis; Quality of Life; dolní končetina; svalová síla; Humans; Intradialytic exercise; odporový trénink; lidé; muscle functions; kvalita života; resistance training; patients